Zastosowanie technik komputerowych w rachunkowości - aspekty dydaktyczne - Andrzejewski, Mariusz; Jonas, Krzysztof (Implementation of Computer-Based Sysytems in Accounting-Didactical Approach, 2005)
The paper deals with problems associated with conducting courses in Accounting when computers and software are involved in the didactical process. The first section emphasizes that class-room software solution reflects the structure of modern accounting. Section 2 describes the need for such courses in Accounting, especially during the latter years and semesters of studies, after lectures on Principles of Accounting and Financial Accounting. Section 3 argues that there is a great need for a good syllabus for course on Implementation of computer-based systems in accounting. Some methodical issues of conducting this kind of courses were also addressed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 15-24